A Simple Procedure for Correcting Loading Effects of Aethalometer Data - Virkkula, Aki; Mäkelä, Timo; Hillamo, Risto; Yli-Tuomi, Tarja; Hirsikko, Anne; Hämeri, Kaarle; Koponen, Ismo K. (Journal of the Air & Waste Management Association (1995), 2007)
A simple method for correcting for the loading effects of aethalometer data is presented. The formula BC(CORRECTED) = (1 + k x ATN) x BC(NONCORRECTED), where ATN is the attenuation and BC is black carbon, was used for correcting aethalometer data obtained from measurements at three different sites: a subway station in Helsinki, an urban background measurement station in Helsinki, and a rural station in Hyytiälä in central Finland. The BC data were compared with simultaneously measured aerosol volume concentrations (V). After the correction algorithm, the BC-to-V ratio remained relatively stable between consequent filter spots, which can be regarded as indirect evidence that the correction algorithm works. The k value calculated from the outdoor sites had a clear seasonal cycle that could be explained by darker aerosol in winter than in summer. When the contribution of BC to the total aerosol volume was high, the k factor was high and vice versa. In winter, the k values at all wavelengths were very close to that obtained from the subway station data. In summer, the k value was wavelength dependent and often negative. When the k value is negative, the noncorrected BC concentrations overestimated the true concentrations.